PEMANFAATAN PENGINDERAAN JAUH UNTUK IDENTIFIKASI PERMUKIMAN KUMUH DAERAH PENYANGGA PERKOTAAN (Studi Kasus : Kecamatan Mranggen Kabupaten Demak) - Rezky Arief Ramadhan; Bitta Pigawati (Department of Urban and Regional Planning, Diponegoro University, 2014)
Mranggen Subdistrict is one of the buffer zone area for Semarang City that slums area can be found. Emergence of slums area in Mranggen Subdistrictis because the impact of increased population in Semarang Capital. Increasing of the settlements area and housing become a logical consequence that comes from the main case. This condition is a major trigger from the formation of slums area. The purpose of this research is to identify characteristics of slums area in Mranggen Subdistrict, as a buffer area for Semarang Capital, with a quantitative approaching method. Instruments used in this research were observation, interview, and questionaire with descriptive and spatial analysis techniques using the Interpretation of Alos satellite imagery to know the distribution of slums area. The results showed that some of the slums area in Mranggen Subdistrict has a bad quality of buildings, semi-permanent and non-permanent buildings still stands, varying distance between the buildings was like (< 1,5 meters, 1,5 – 3,0 meters, and > 3,0 meters). Location of the slums area is very strategic that so many people could make an easy access towards the working place. Condition of the road was good, but condition of the drainage system, clean water, and sanitation were bad. Many house that have not been certified yet, low level of population growth and density, low rate income, also migrants people that prefers to live in this location rather than the other places, because near from their working place. So, strategic ways to handle slums area in Mranggen Subdistrict can be done using poverty development, community based development, and guided land development approach.